Reevaluating Bloom’s Taxonomy: What Measurable Verbs Can and Cannot Say about Student Learning - Claudia J. Stanny (Education Sciences, 2016)
Faculty and assessment professionals rely on Bloom’s taxonomy to guide them when they write measurable student learning outcomes and describe their goals for developing students’ thinking skills. Over the past ten years, assessment offices and teaching and learning centers have compiled lists of measurable verbs aligned with the six categories that comprise Bloom’s taxonomy. The author analyzed 30 compilations posted on web sites and evaluated how well these verbs aligned with categories in Bloom’s taxonomy. The author discusses the value of Bloom’s taxonomy as a heuristic for writing student learning outcomes and other factors faculty should consider when they articulate learning outcomes to describe levels of expertise attained by students who complete an associate’s, bachelor’s, or graduate degree.